2020
DOI: 10.1021/acs.jafc.0c00225
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome-Based Diagnostic Model to Predict Coronary Artery Disease

Abstract: In the present study, we aimed to characterize gut microbiome and develop a gut microbiome-based diagnostic model in patients with coronary artery disease (CAD). Prospectively, we collected 309 fecal samples from Central China and Northwest China and carried out the sequencing of the V3−V4 regions of the 16S rRNA gene. The gut microbiome was characterized, and microbial biomarkers were identified in 152 CAD patients and 105 healthy controls (Xinjiang cohort, n = 257). Using the biomarkers, we constructed a dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 31 publications
8
27
0
Order By: Relevance
“…Four studies were excluded due to insufficient information pertaining to the inclusion criteria, and a second article by the same authors was found to be a repetitive report based on a partial dataset. In total, 16 publications, reporting on 16 cohort studies, were selected for inclusion in the analysis [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were excluded due to insufficient information pertaining to the inclusion criteria, and a second article by the same authors was found to be a repetitive report based on a partial dataset. In total, 16 publications, reporting on 16 cohort studies, were selected for inclusion in the analysis [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, for the screening of marker bacteria, we employed a mechanical learning model to screen for important bacteria. For the calculation of the probability of disease (POD) index, we performed logarithmic transformation on the bacterial abundance, and combined logistics regression to calculate the probability as the POD index [20].…”
Section: Microbiome Data Analysismentioning
confidence: 99%
“…Subsequently, we performed logarithmic transformation on the microbial abundance of these 12 genera microorganisms. We calculated the POD value in combination with logistics regression [20], and established the nomogram diagnostic model in combination with age, gender (if female), and clinical variable indicators such as the denial from the diagnosis of hypertension and fasting blood glucose (See Fig. 7A).…”
Section: Nomogram Prediction Of Dmmentioning
confidence: 99%
“…The gut microbiota, despite its complexity and great variation between individuals, was shown to be predictive of various intestinal diseases and conditions, such as irritable bowel syndrome (IBS) [ 3 ], Crohn’s disease [ 4 , 5 ], and colorectal cancer [ 6 ]. Interestingly, the composition of the gut microbiome also predicts some non-intestinal illnesses, such as coronary artery disease [ 7 ], liver fibrosis [ 8 ], metabolic diseases/obesity [ 9 ], insomnia [ 10 ], and bipolar depression [ 11 ]. Another classification setting is the detection of contamination in samples.…”
Section: Introductionmentioning
confidence: 99%
“…Random forest (RF) algorithm [24] was chosen for the classification task. RFs are highly used machine learning algorithms for microbiome classification [3][4][5][6][7][8][9][10][11] due to the limited number of model parameters and simple results interpretation.…”
Section: Introductionmentioning
confidence: 99%